ANALISIS SEMIOTIKA PESAN MORAL DARI FILM MIRACLE IN CELL NO 7 "VERSI INDONESIA" - Banjarnahor, Tia Andianty; Cindoswari, Ageng Rara (SCIENTIA JOURNAL, 2023)
Film is a new form of media that is used to provide technical information to the public as wellas traditional forms of entertainment. The movie "Miracle in Cell No. 7" in Indonesian depictselements of miraculous and good fortune, which is an intriguing subject to research. Thisstudy used descriptive research, which strives to provide methodical, factual, and accurateexplanations of the facts as well as connections between the phenomena underinvestigation. Roland Barthes' semiotics analysis, which includes the film's connotations,denotations, and myths, was used to conduct qualitative research on the moral themes inthe Indonesian version of "Miracle in Cell No. 7"